The Development of Website-Based Worksheets on Flat 3D Shapes Topic - Erita, Selvia; Nelda, Hikma; Ningsih, Febria (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2022)
The development of website-based worksheets represents an innovation to enhance the quality of education during the Covid-19 pandemic. The aim of this study is to outline the process of creating and assessing the feasibility of website-based worksheets on the topic of flat 3D shapes. The ADDIE model, consisting of five phases: analysis, design, development, implementation, and evaluation, was used in this research. The instruments utilized included media and content validation questionnaires, teacher and student response questionnaires, and tests. The findings indicate that the website-based worksheets on flat 3D shapes fulfilled the criteria for validity, practicality, and effectiveness. The average validity index of the website-based worksheets was in the valid category, while the average of teacher and student responses to the worksheets was in the practical category. Furthermore, based on the average student learning outcomes, the website-based worksheets were found to be effective. As such, these worksheets can be adapted for use with other materials by adjusting the design and content to suit the needs and characteristics of students, leading to more effective and efficient learning.